Preeclampsia as a Risk Factor for Future Cardiovascular Disease : A Comprehensive Systematic Review - Riski Amira; Putri Rahmi Maharani; Robby Rachman; Kevin Habib Alhuda (The International Journal of Medical Science and Health Research, 2026)
Introduction: Preeclampsia (PE) affects 2–8% of pregnancies and is a leading cause of maternal morbidity. While its acute risks are well-recognized, emerging evidence suggests PE leaves a lasting imprint on maternal cardiovascular health. However, the magnitude of risk for specific cardiovascular outcomes, the role of PE severity and recurrence, and the underlying mechanistic pathways remain incompletely synthesized. Methods: This systematic review synthesizes 80 studies (cohort, case-control, meta-analyses, systematic reviews) identified through structured screening. Inclusion required documented PE diagnosis, a normotensive control group, cardiovascular outcomes (events or risk factors), ≥1 year postpartum follow-up, and separate analysis of PE. Data were extracted on composite cardiovascular disease (CVD), cardiovascular mortality, hypertension, stroke, subclinical atherosclerosis, cardiac dysfunction, endothelial function, and metabolic factors. Results: Women with prior PE have approximately double the risk of composite CVD (RR 2.33, 95% CI 1.95–2.78) and cardiovascular death (RR 1.97–2.29) [1,5]. Heart failure risk is highest (RR 2.47–4.19) [1,6,7]. Chronic hypertension risk is increased 3- to 4-fold (RR 3.70) [2,29]. Stroke risk rises approximately 1.8- to 2-fold [4,43]. Severe, early-onset, or recurrent PE confers substantially higher risk (e.g., severe PE: RR 5.36 for cardiac disease) [5]. Subclinical atherosclerosis (CIMT SMD 0.63; CAC OR 1.57) [16], persistent endothelial dysfunction (impaired FMD) [13], adverse metabolic profiles (higher BP, BMI, lipids, insulin resistance) [18], and subclinical left ventricular dysfunction (worse GLS) [15,20] are consistently observed. Risk emerges within 1–3 years and persists for decades [3]. Discussion: PE acts as both a marker of pre-existing cardiovascular susceptibility and an independent vascular injury event (“two-hit” model). The dose-response relationship with severity/recurrence and the early onset of risk support causality. Heterogeneity across studies is largely explained by differences in PE subtype, follow-up duration, and measurement techniques. Current guidelines recognize PE as a CVD risk factor, yet postpartum screening and prevention remain underutilized. Conclusion: Preeclampsia is a significant, independent, and dose-dependent risk factor for future CVD, hypertension, stroke, and cardiovascular mortality. Risk manifests through persistent endothelial dysfunction, accelerated atherosclerosis, and adverse metabolic remodeling. Early postpartum intervention and long-term surveillance are urgently needed.